Medicare Plans’ Adoption of Special Supplemental Benefits for the Chronically Ill for Enrollees With Social Needs - Meyers, David J. (JAMA Netw Open, 2020)
This cross-sectional study assesses the extent to which Medicare plans have offered Special Supplemental Benefits for the Chronically Ill for enrollees with social needs.